Action, praxis, history: Some remarks on the merleau-pontyan concept of “institution” (Nóema, 2022)
The aim of this paper is to explore the merleau-pontyan concept of “institution” by focusing on its development along the 1954-55’s course held by Merleau-Ponty at the Collège de France, titled L’institution, la passivité. The paper intends to show how, by means of this notion, it is possible to think both the active and passive sides of action within individual action, praxis and therefore history. The essay starts with an overview of Merleau-Ponty’s critiques to the sartrian philosophy developed in Adventures of Dialectic, in order to show Merleau-Ponty’s polemical aim against which Merleau-Ponty develops his conception of action. After that, it deepens Merleau-Ponty’s notion of institution following the omonimous course. Finally, the paper tries to describe the conception of history that can be derived from this framework. In the final lines, the paper attempts to open up the concept of institution at the light of some contemporary theoretical problems, such as the problem of agency.
Keywords: institution; praxis; hystory; phenomenology; Maurice Merleau-Ponty